Female and migrant entrepreneurship in SOS children's villages in the Lambayeque region, Peru - Silvia Lourdes Vidal-Taboada; Marina Fernández-Miranda; Luis Alberto Vásquez-Caballero (Administrative Sciences, 2024)
This quantitative research analyzes the entrepreneurial competencies of in-migrant women in the Children's Village of the Lambayeque Region. With a sample of 79 women, 39 Peruvian and 40 Venezuelan, online surveys and observation forms were operated for 18 months (2021-2022). Using a Likert scale of 55 questions and nine dimensions, competencies such as opportunity seeking, risk anticipation, persistence, self-exertion, and more were assessed. Data were analyzed using correlations, ANOVA, logistic regression, and principal component analysis (PCA). The results revealed significant differences between nationalities, with Venezuelan women having higher competencies. The study identified two principal components that explain 57.663% of the total variance, representing initiative and quality, as well as control and responsibility. These findings suggest the need for specific training programs to strengthen the entrepreneurial competencies of these women. The inductive methodology and quantitative analysis provided a clear vision of entrepreneurial competencies, contributing to the improvement of support and training programs
Keywords: 350; women entrepreneurs; immigrant women; entrepreneurial skills; unemployment; qualityof life